IFRS Implementation in Turkey: Benefits and Challenges - Oğuzhan Bahadır; Volkan Demir; Aslı Gül Öncel (Journal of Accounting and Management Information Systems (JAMIS), 2016)
This paper presents a study of the implementation process for International Financial Reporting Standards (IFRS) in Turkey. The study analyzes the application of IFRS in Turkish publicly traded companies which have been preparing their financial statements under IFRS since 2005, and highlights some key issues that are arising in IFRS implementation by using a questionnaire-based survey, which was completed by 90 Turkish listed firms. The benefits and challenges of IFRS implementation are analyzed, as well as the level of understanding and experience with IFRS, and the perception of the accounting quality provided by IFRS. According to the results, the implementation of IFRS is believed to improve financial reporting by increasing the comparability, quality and transparency of financial statements. However, the lack of IFRS implementation guidance, sufficient sector-adopted regulations, and the difficulty in applying fair value concept are considered major challenges to IFRS implementation in Turkey.
Keywords: M41; 650; IFRS implementation; Turkish GAAP; accounting quality; survey